Extrapolation and interpolation in generalized Orlicz spaces - David Cruz-Uribe; Peter Hästö (AMER MATHEMATICAL SOC, 2022)
We prove versions of the Rubio de Francia extrapolation theorem in generalized Orlicz spaces. As a consequence, we obtain boundedness results for several classical operators as well as a Sobolev inequality in this setting. We also study complex interpolation in the same setting and use it to derive a compact embedding theorem. Our results include as special cases classical Lebesgue and Sobolev space estimates and their variable exponent and double phase growth analogs.